AIFM1 is a component of the mitochondrial disulfide relay that drives complex I assembly through efficient import of NDUFS5. (20th July 2022) - Salscheider, Silja Lucia; Gerlich, Sarah; Cabrera‐Orefice, Alfredo; Peker, Esra; Rothemann, Robin Alexander; Murschall, Lena Maria; Finger, Yannik; Szczepanowska, Karolina; Ahmadi, Zeinab Alsadat; Guerrero‐Castillo, Sergio; Erdogan, Alican; Becker, Mark; et al.
Abstract: The mitochondrial intermembrane space protein AIFM1 has been reported to mediate the import of MIA40/CHCHD4, which forms the import receptor in the mitochondrial disulfide relay. Here, we demonstrate that AIFM1 and MIA40/CHCHD4 cooperate beyond this MIA40/CHCHD4 import. We show that AIFM1 and MIA40/CHCHD4 form a stable long‐lived complex in vitro, in different cell lines, and in tissues. In HEK293 cells lacking AIFM1, levels of MIA40 are unchanged, but the protein is present in the monomeric form. Monomeric MIA40 neither efficiently interacts with nor mediates the import of specific substrates. The import defect is especially severe for NDUFS5, a subunit of complex I of the respiratory chain. As a consequence, NDUFS5 accumulates in the cytosol and undergoes rapid proteasomal degradation. Lack of mitochondrial NDUFS5 in turn results in stalling of complex I assembly. Collectively, we demonstrate that AIFM1 serves two overlapping functions: importing MIA40/CHCHD4 and constituting an integral part of the disulfide relay that ensures efficient interaction of MIA40/CHCHD4 with specific substrates. Synopsis: Mitochondrial disulfide relay is essential for protein import into the mitochondrial intermembrane space and thus respiratory chain assembly. Here, AIFM1 is found to cooperate with the disulfide relay to accelerate the import of the complex I subunit NDUFS5. AIFM1 is a part of the mitochondrial disulfide relay mediating protein import into the mitochondrial intermembrane space. AIFM1 forms a stable 1‐to‐2 complex with MIA40/CHCHD4. The complex of AIFM and MIA40/CHCHD4 is critical for mitochondrial import of specific MIA40/CHCHD4substrates. In complex I, the import of NDUFS5 is most affected upon AIFM1 loss and leads to complex I assembly stalling. Abstract : The mitochondrial intermembrane space protein AIFM1 not only mediates MIA40/CHCHD4 import but also that of its substrates.